Onciderini Thomson, 1860 (Coleoptera: Cerambycidae: Lamiinae) types of The Natural History Museum (BMNH) - Nearns, Eugenio H.; Barclay, Maxwell V.l.; Tavakilian, Gérard L. (Zootaxa, 2014)
The primary types of Onciderini Thomson, 1860 deposited at The Natural History Museum (BMNH), London, United Kingdom, are catalogued and illustrated. Data on the original combination, current name, and type locality are verified and presented. There are 39 primary types of Onciderini including 11 in Oncideres Lacordaire, 1830; and three each in Hesycha Fairmaire & Germain, 1859; Hypselomus Perty, 1832; Lamia Fabricius, 1775; and Tybalmia Thomson, 1868. Of the 39 primary types, 17 were described by H. W. Bates and seven by F. P. Pascoe. Five lectotypes are designated. Notes on additional Onciderini types once believed to be deposited at the BMNH are presented.